Forecast errors and the macroeconomy - a non-linear relationship? - Ulrich Fritsche; Joerg Doepke (Hamburg University, Department Economics and Politics, 2006)
The paper analyses reasons for departures from strong rationality of growth and inflation forecasts based on annual observations from 1963 to 2004. We rely on forecasts from the joint forecast of the so-called "six leading" forecasting institutions in Germany and argue that violations of the rationality hypothesis are due to relatively few large forecast errors. These large errors are shown - based on evidence from probit models - to correlate with macroeconomic fundamentals, especially on monetary factors. We test for a non-linear relation between forecast errors and macroeconomic fundamentals and find evidence for such a non-linearity for inflation forecasts.
Keywords: E32; E37; C52; C53; 330; forecast error evaluation; non-linearities; business cycles